Is Diet A Contributing Factor To Infertility? - Ufaque Batool K Samo; Kausar Abbas Saldera; Rizwan Ali Lakho; Gul Mohammad Kazi; Maliha Shamim; Sarah Hussain Sharif (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Objective: To evaluate the effect of dietary trans-unsaturated fatty acids (TFAs) on ovulatory infertility in young unmarried females. Methods: This cross-sectional study was conducted from 1 august 2023 to 31 December 2023 at the Basic Medical Science Institute (BMSI), Jinnah Postgraduate Medical Center Karachi. All healthy unmarried females aged 15-25 were included in the study. Females with a family history of infertility, having existing comorbidity, history of irregular menstruation cycle or hormonal replacement therapy, were excluded. Based on the Food frequency questionnaire score, 300 subjects were divided into 3 groups, Group A were low trans fats Consumers (Score 0-170), Group B was moderate trans fats consumers (Score 171-340) and Group C were high trans fats consumers (Score 341-500). The analysis of results was carried out on SPSS Software version 22. Results: The study's 300 respondents, who ranged in age from 16 to 25, had a mean age of 21.8 years. Fifteen per cent of those in group "A" had abnormal HDL, 22% had bad LDL, and 23% had abnormal TGA, while 17% had abnormal cholesterol. An abnormal TGA, abnormal HDL, abnormal LDL, and abnormal 31% of the participants in group "B" exhibited abnormal cholesterol levels. A significant correlation between oxidative stress and hormonal indicators was found in three groups: "A" (13%) had aberrant LH, "20%" had abnormal FSH, "11%" had abnormal serum estrogen, "10%" had abnormal serum progesterone, and "C" (49% had abnormal LH, FSH, estrogen, and progesterone). Food frequency questionnaire (FFQ ) scores had a 25% positive correlation with cholesterol, a 40% negative correlation with HDL, a 31% positive correlation with LDL, and a 39% positive correlation with biochemical and hormonal indicators. Conclusion: Trans fats diets significantly increase the risk of ovulatory infertility and reproductive failure in young females